A new sRNA‐mediated posttranscriptional regulation system for Bacillus subtilis. Issue 12 (1st October 2018) - Yang, Sen; Wang, Yang; Wei, Chaobao; Liu, Qingtao; Jin, Xuerong; Du, Guocheng; Chen, Jian; Kang, Zhen
Abstract: Many genetic tools for gene regulation have been developed during the past decades. Some of them edit genomic DNA, such as nucleotides deletions and insertions, while the others interfere with the gene transcriptions or messenger RNA translation. Here, we report a posttranscriptional regulation tool which is termed "Modulation via the small RNA (sRNA)‐dependent operation system: MS‐DOS" by engineering the type I toxin–antitoxin system in Bacillus subtilis . MS‐DOS depends simply on insertion of an operation region (OPR; partial toxin‐encoding region) downstream of a genomic open reading frame of interest and overexpression of the coupling antitoxin sRNA from a plasmid. Pairing between the OPR and the sRNA will trigger the RNAse degradation of the transcripts of selected genes. MS‐DOS allows for the quantitative, specific, and reversible knockdown of single or multiple genomic genes in B. subtilis . We also showed that the truncated antitoxin SR4 with 53 nt length is sufficient to repress gene expression. Superior to other existing RNA based interfering systems, MS‐DOS allows simultaneous knockdown of multiple genes with effortless expression of a single antitoxin RNA. This sRNA‐guided repression system will further enrich the gene regulation tools and expand the gene regulation flexibility. Abstract : Many genetic tools for gene regulation have been developed during the past decades. Some of them edit genomic DNA, such as nucleotides deletions and insertions, whereas the others interfere with the gene transcriptions or messenger RNA translation. Here, we report a posttranscriptional regulation tool which is termed "Modulation via the small RNA (sRNA)‐dependent operation system: MS‐DOS" by engineering the type I toxin–antitoxin (TA) system in Bacillus subtilis .